Credit Alternatives in Rural Finance : Rinancial Leasing - Kloeppinger-Todd, Renate (World Bank, Washington, DC, 2012)
Enterprises use credit to acquire productivity-enhancing assets. Rural enterprises in developing economies, however, often lack access to the credit they need. Key reasons for this lack of access include the low level and scattered nature of economic activity in rural areas, the enterprises' lack of collateral, inadequate capacity among the country's lenders to lend in rural areas, and legal and policy environments that discourage lending to rural enterprises. Traditionally, leasing has served as an alternative to credit for urban enterprises, but generally it has not been a feasible option for rural enterprises. This paper argues that rural leasing can be viable and highlights the key factors to facilitate successful rural leasing, including the advantages of leasing, an enabling environment, and institutional support. The paper concludes that leasing is a viable tool to finance rural assets.